PENGEMBANGAN SOAL PENALARAN MATEMATIS SISWA PADA MATERI PELUANG - Dea Meilisa Putri; Yuriska Destania (Alifmatika (Jurnal pendidikan dan pembelajaran Matematika), 2020)
This research aimed to produce the product in the form of questions of valid and practical students' mathematical reasoning skills. The subjects of this study were 6 students of grade VIII to saw the readability of the given questions. The research and development method used the Tessmer model consisted of preliminary stage self-evaluation, expert review, one-to-one, small group, and field test. At the preliminary stage, there were two stages, namely preparation and design. The preparation of the stage was analyzing the curriculum, materials, and students' level. The design stage was done to design as questions of mathematical reasoning capabilities. The Self Evaluation stage was conducted after designed the questions of mathematical reasoning skills there were 15 questions and assesses whether the question meets the material, construction, and language. After evaluating the questions that would be validated by the expert reviewer and would be validated 3 times. After 14 questions validated that would be tested on 6 students to saw the practicality of the question through the student's responded questionnaire that was provided. Based on the result of the readability tested, the conclusion development of the questions from numbers 1 to 14 in the category of practicality were intervals of 4 ≤ RP (Produk) ≤ 5 which were classified as Very Practical.